Correlation Between Patient Characteristics and Dose Area Product (DAP) in Digital Chest Radiography - Asriningrum, Surdiyah; Septapati, Guntur; Nilasari, Vini; Suwandi; Rizki, Rd. Riri (International Journal of Health, Medicine, and Sports, 2025)
Posteroanterior (PA) chest radiography is one of the most commonly performed radiographic procedures to evaluate the lungs and heart. Although considered a low-dose examination, repeated and uncontrolled radiation exposure may still pose risks to patient safety. Therefore, dose estimation is important to ensure that exposure techniques comply with radiation protection principles, particularly the ALARA principle (As Low As Reasonably Achievable).This study aims to estimate the radiation dose using the Dose Area Product (DAP) parameter and analyze the correlation between patient body weight and DAP values. A total of 260 patients undergoing PA chest radiography were included in this retrospective study. Patient characteristics such as body weight, age and sex were recorded along with exposure parameters (kV and mAs) . A normality test was performed, and due to non-normal data distribution, the Spearman correlation test and the Mann Whitney U test were used for statistical analysis. The results showed a statistically significant correlation between body weight and DAP values (ρ = 0.214, p = 0.001), indicating that patients with higher body weight tend to receive slightly higher radiation doses. No significant correlation was found between age and DAP (ρ = –0.083, p = 0.184). Additionally, the comparison of DAP values between male and female patients showed no statiscally significant difference (p = 0.051), although male patients had slightly higher median DAP values.